2000
DOI: 10.1359/jbmr.2000.15.8.1564
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Vertebral Deformities in Older Men and Women

Abstract: The objectives of this study were to ascertain the prevalence of the number and severity of vertebral deformities in elderly people and determine the extent to which these are associated with several aspects of functioning. The study was conducted in a subsample of the Longitudinal Aging Study Amsterdam (LASA) consisting of 527 participants (260 men and 267 women), aged 65 years or over. Lateral radiographs of the spine (T4-L5) were made of each participant and a semiquantitative method was used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
0
16

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(130 citation statements)
references
References 38 publications
(45 reference statements)
7
105
0
16
Order By: Relevance
“…Previous research has confirmed changes in muscle recruitment as a consequence of pain [19,21,23,48]. Other factors related to vertebral fractures such as decreased mobility and fear of falling could also influence muscle activation characteristics [35]. Furthermore, individuals with vertebral fractures demonstrate lower backextensor and systemic strength compared to individuals without fractures [9,42].…”
Section: Discussionmentioning
confidence: 89%
“…Previous research has confirmed changes in muscle recruitment as a consequence of pain [19,21,23,48]. Other factors related to vertebral fractures such as decreased mobility and fear of falling could also influence muscle activation characteristics [35]. Furthermore, individuals with vertebral fractures demonstrate lower backextensor and systemic strength compared to individuals without fractures [9,42].…”
Section: Discussionmentioning
confidence: 89%
“…A possible explanation of this finding may be that some mild deformities are not true vertebral osteoporotic fractures but may be anatomic variants or degenerative abnormalities. Pluijm et al [28] in a longitudinal study reported that, in contrast with more severe deformity, the presence of mild vertebral deformities only was not significantly associated with any of the outcome measures of functioning and well-being. In our study the domain ''pain'' did not show any differences between patients with or without vertebral fractures or among patients according to the number and grades of vertebral fractures.…”
Section: Discussionmentioning
confidence: 97%
“…Spinal compression fracture and femoral neck fracture in patients with osteoporosis are common and negative factors associated with a decrease in QOL [1,2]. However, many elderly people have abnormal posture, represented by hyperkyphosis, without pain or a history of such fractures.…”
Section: Introductionmentioning
confidence: 99%